2013
DOI: 10.4103/0971-3026.113621
|View full text |Cite
|
Sign up to set email alerts
|

Appearances of the circumcaval ureter on excretory urography and MR urography: A single-center case series

Abstract: Objectives:To describe Magnetic Resonance Urography (MRU) appearances of the circumcaval ureter, a rare congenital cause of hydronephrosis.Materials and Methods:Seven cases of circumcaval ureter, suspected on intravenous urography (IVU), underwent subsequent static MRU using heavily T2-weighted sequences.Results:The various appearances of circumcaval ureter on IVU and MRU were studied and compared. The circumcaval portion of the ureter was especially well seen on axial MRU sections, though this portion was rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In 2002, Uthappa et al reported the potential of MRI to diagnose circumcaval ureter with equal effectiveness of spiral CT but without the radiation risk [13]. The same has been confirmed by Muthusami et al [14]. MRI can also be used in those patients with poor renal function as MR urogram, in pregnant women and in children.…”
Section: Radiologic Diagnosismentioning
confidence: 89%
“…In 2002, Uthappa et al reported the potential of MRI to diagnose circumcaval ureter with equal effectiveness of spiral CT but without the radiation risk [13]. The same has been confirmed by Muthusami et al [14]. MRI can also be used in those patients with poor renal function as MR urogram, in pregnant women and in children.…”
Section: Radiologic Diagnosismentioning
confidence: 89%
“…Hence, it can be combined with antegrade and ascending urography to confirm the diagnosis but is an invasive procedure. [11][12][13] Abdominopelvic CT scan is helpful in excluding these conditions. Spiral CT scan may define ureter and inferior vena cava anomalies and is considered as an investigation of choice.…”
Section: Discussionmentioning
confidence: 99%
“…In 2002, Uthappa et al reported the potential of MRI to diagnose circumcaval ureter with equal effectiveness of spiral CT but without the radiation risk (Uthappa et al, 2002). The same has been confirmed by (Muthusami & Ramesh, 2013). MRI can also be used in those patients with poor renal function as MR urogram in pregnant women and children.…”
Section: • Less Common (10%)mentioning
confidence: 94%